The firm - Rudin, Scott; Davis, John; Pollack, Sydney; Paramount Pictures (Hollywood, California : Paramount Pictures, 2000)
Cruise plays Mitch McDeere, a brilliant and ambitious Harvard Law grad. Driven by a fierce desire to bury his working-class past, Mitch joins a small, properous Memphis firm that affords Mitch and hi swife (Jeanne Tripplehorn) an affluent lifestyle beyond their wildest dreams. But when FBI agents confront him with evidence of corruption and murder within the firm, Mitch sets out to find the truth in deadly crossfire between the FBI, the Mob, and a force that will stop at nothing to protect its interests-The Firm.
Originally released as a motion picture in 1993
Based on the book by John Grisham
Editor, William Steinkamp and Frederic Steinkamp ; production designed, Richard Macdonald ; director of photography, John Seale ; screenplay by, David Rabe, Robert Towne and David Rayfiel
Cast : Tom Cruise, Jeanne Tripplehorn, Ed Harris, holly Hunter, Hal Holbrook, David Strathairn
Keywords: Law firms -- United States -- Drama; Lawyers -- United States -- Drama; Corruption investigation -- United States -- Drama